PANDANGAN PIHAK KUA KASIHAN, BANTUL, YOGYAKARTA TENTANG KAWIN HAMIL - Yustika, Dian Andromeda (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
Intercourse is performed in the absence of legal marriage is called fornication. Committed adultery often leads topregnancy . Marriage in the state of pregnant women have become pregnant as a result of adultery called mating.KUA, as the institution of marriage registrar, shall note any marriage, including marital pregnant women due toadultery. KUA Kasihan, Bantul notes that pregnant women due to adultery marriage is allowed, but only withmen who impregnate. The reason is for the benefit of the child and the child’s status nasab. The reference is toArticle 53 KHI and does not conflict with the contents of Surah an -Nur verse 3 This is an application of thetheory of welfare and maqashid ash- Shari’ah. Marriage of pregnant women with men who did not impregnate cannot be implemented, because madharatnya greater than maslahatnya, namely aduknya mixed descent. This paperexamines how the KUA opinion about marriage pregnant, including the basis and reasons used in pregnantwomen due to marry adultery is in KUA Kasihan, Bantul.[Persetubuhan yang dilakukan tanpa adanya perkawinan yang sah dinamakan perzinaan. Perzinaanyang dilakukan tidak jarang menyebabkan kehamilan. Perkawinan dalam keadaan wanita telah hamilakibat zina dinamakan kawin hamil. KUA, sebagai lembaga pencatat perkawinan, berkewajibanmencatat setiap perkawinan, termasuk perkawinan wanita hamil akibat zina. KUA Kecamatan Kasihan,Bantul memberi catatan bahwa perkawinan wanita hamil akibat zina diperbolehkan, namun hanyadengan laki-laki yang menghamili. Alasannya ialah demi kemaslahatan anak dan status nasab bagianak. Acuannya ialah pasal 53 KHI dan tidak bertentangan dengan isi Surat An-Nûr ayat 3. Hal inimerupakan penerapan teori kemaslahatan dan maqashid asy-syari’ah. Perkawinan wanita hamildengan laki-laki yang tidak menghamili tidak dapat dilaksanakan, karena lebih besar madharatnyadaripada maslahatnya, yakni bercampur aduknya keturunan. Tulisan ini mengkaji bagaimana pendapatpihak KUA tentang kawin hamil, termasuk juga dasar dan alasan yang dipakai dalam menikahkanwanita hamil akibat zina yang ada di KUA Kecamatan Kasihan, Bantul.